Document Management System – A Way to Digital Transformation - Jordan, Sandra; Sternad Zabukovšek, Simona; Šišovska Klančnik, Irena (Naše gospodarstvo/Our economy, 2022)
One of the key activities of any company is the management of documents, which are created on a daily basis. Classic document management cannot follow the needs of the market for companies with a desire to be agile and modern. Therefore, companies need to offer employees a solution that allows them to carefully store and archive documentation, while at the same time giving them enough time to perform their main daily tasks. Electronic management of documents not only influences companies’ workflows, savings and adaptions to market needs but also influences their digital transformation. It is also necessary to consider the influences on the environment. The influence of the production and use of paper in daily business has burdened the environment a lot in the past and it is about time that this matter is addressed. Implementation of a document management system (DMS) is now almost a must-have for companies wanting to be competitive in the market and with a desire to digitalise its processes, and is also surely a good step in the right direction for the environment. The aim of this paper is to define the advantages of disadvantages of a DMS as part of companies’ digital transformation as well as to provide an overview of the process of implementation and to analyse future trends and predictions in this field. For better understanding, the authors also included some examples of the implementation of a DMS in Slovenian companies.